THE PSYCHOLOGICAL ASPECTS OF THE PERSONALITY OF THE CONVICTED PERSON - Dilbar Suyunova (PT. Antis International Publisher, 2024)
The study of the psychological aspects of a person and his activities in the context of legal regulation is a legal psychology, knowledge of which is an indicator of the professional competence of a lawyer. Recently, at the intersection of investigative, operational-search and forensic psychology, an independent direction has been developed - criminal psychology, the subject of which is the study of the psychology of the criminal, and his illegal behavior. In this research, the author analyzes the institution of a criminal record through the prism of the psychological characteristics of the criminal, his perception of his own status as a convicted person. The article proposes to revise the basic principles of criminal law relating to a criminal record, in order to protect the rights and interests of a person, to create civil and social institutions with the functions of psychological relaxation and rehabilitation of persons who have violated the law.